2022
DOI: 10.1155/2022/6445022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Density and Volume Fraction of Void, and Mechanical Characteristics of Areca Nut Leaf Sheath Fiber-Reinforced Polymer Composites

Abstract: Natural fiber-reinforced polymer composite is a rapidly growing topic of research due to the simplicity of obtaining composites that is biodegradable and environmentally friendly. The resulting composites have mechanical properties comparable to synthetic fiber-reinforced composites. In this regard, the present work is formulated with the objectives related to the development, characterization, and optimization of the wt% of reinforcements and the process parameters. The novelty of this work is related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In a study of the tensile characteristics of areca fiber composites, it was found that chemical treatment of the fiber could change the mechanical properties, and the areca fiber treatment increased the mechanical strength when compared to non-alkali fibers. When compared with untreated fibers, fibers treated with alkali proved a significant increase in elastic strength [7].…”
Section: Arti C L E I N F O R M a T I O N Abstractmentioning
confidence: 91%
See 1 more Smart Citation
“…In a study of the tensile characteristics of areca fiber composites, it was found that chemical treatment of the fiber could change the mechanical properties, and the areca fiber treatment increased the mechanical strength when compared to non-alkali fibers. When compared with untreated fibers, fibers treated with alkali proved a significant increase in elastic strength [7].…”
Section: Arti C L E I N F O R M a T I O N Abstractmentioning
confidence: 91%
“…When the fiber weight fraction reaches the required percentage, the mechanical strength of the composite specimen increases again. Therefore, it can be estimated that a fiber weight percentage of 50% is an important ingredient for the composite [15].…”
Section: Modulus Of Elasticitymentioning
confidence: 99%
“…The density of FRP materials is influenced by factors such as the type of fibers and resin used, void content, and manufacturing process. Voids within composites can significantly reduce density and affect mechanical characteristics, leading to reduced fatigue resistance, increased susceptibility to weathering, and varied strength properties [16]. Pultruded FRP materials generally have lower density than traditional construction materials like steel or concrete, contributing to their lightweight nature.…”
Section: Densitymentioning
confidence: 99%
“…Various methods, such as layer-by-layer stacking, arranging different bres in a single layer, varying the bre orientation, and selective bre placement, are employed for hybridization. [32][33][34][35][36] At the nanoscale, nano-llers can be added to create hybrid nanocomposites, with their properties inuenced by the choice of nano-ller, manufacturing method, dispersion, and interaction between bres and the matrix. [37][38][39][40][41] The addition of FA, red mud and other discernible wastes causing threats to environment, as ller materials to a polymer matrix is a novel research area, since ndings on the effectiveness of utilizing these discernible wastes from human activities are still in their nascent stage, and only incipient information is available.…”
Section: Introductionmentioning
confidence: 99%